2004
DOI: 10.2466/pms.98.2.542-550
|View full text |Cite
|
Sign up to set email alerts
|

Human Pulling Strengths in Different Conditions of Exertion

Abstract: This study tested 29 young Taiwanese men and 31 young Taiwanese women to examine the effects of pulling type (one-handed and two-handed) and height (48 cm, 84 cm, 120 cm, and 156 cm) on maximum horizontal isometric pulling strengths. Analysis showed differences in pulling strength between one-handed and two-handed efforts were surprisingly small for free pulling postures. The pulling strength decreased significantly with pulling height. The highest pulling strength was approximately two to three fold the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Currently, most of the push and pull strength literature has focused on the determining hand strength under various conditions; including upper limb posture and end-effector (such as fastener, clips and end-connectors) height. Specifically, Kumar (1995) and Cheng and Lee (2004) examined pulling strength at various handle heights, and MacKinnon (1998) studied the same variable but while standing and sitting. In addition, Fothergill et al (1996) investigated how the end-effector in combination with height influenced overall pull strength.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of the push and pull strength literature has focused on the determining hand strength under various conditions; including upper limb posture and end-effector (such as fastener, clips and end-connectors) height. Specifically, Kumar (1995) and Cheng and Lee (2004) examined pulling strength at various handle heights, and MacKinnon (1998) studied the same variable but while standing and sitting. In addition, Fothergill et al (1996) investigated how the end-effector in combination with height influenced overall pull strength.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule of thumb, female strength is two-thirds the strength of males [ 11 ]. In general, the percentage of female to male strength ranges from 45% to 80%, depending on the muscle groups or types of maneuvers [ 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. For example, the strengths of females were found to be 53% and 48% of the strength of males for pulling and pushing in sitting positions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also investigated the effect on strength caused by the height above the ground at which the exertion was made (Yates, Kamon, Rodgers, & Champney, 1980;Mital, 1984;Cheng & Lee, 2004). Yates, et al (1980) found that upper-body strength (e.g., shoulder strength) was a limiting factor when determining acceptable loads above the waist level.…”
mentioning
confidence: 99%